The Effect of Probiotic Bacteria Lactobacillus Spp. And Bifidobacterium Spp. as A Novel Effective Therapy for Seizures in Epilepsy: A Systematic Review of Preclinical Study Designs - Rince Restiviona; Cimi Ilmiawati; Mayetti Akmal; Yuliarni Syafrita (Indonesian Journal of Global Health Research, 2025)
Epilepsy is a chronic neurological disorder characterized by recurrent seizures due to abnormal electrical activity in the brain. The seizure mechanism involves neurotransmitter imbalance, oxidative stress, and neuroinflammation. Recent studies highlight the role of the gut–brain axis, emphasizing probiotics such as Lactobacillus spp. and Bifidobacterium spp., which potentially stabilize the nervous system through microbiota modulation and anti-inflammatory effects. This review aims to systematically assess preclinical evidence on the efficacy of Lactobacillus spp. and Bifidobacterium spp. as adjunctive therapies to reduce seizures in epilepsy through molecular and gut–brain axis mechanisms. This systematic review followed PRISMA guidelines, with literature searches performed in Google Scholar, PubMed, Taylor & Francis, and ScienceDirect, including publications from 2015 to 2025 (1576 articles to 13 articles), and inclusion criteria based on the PICOS framework. Risk of bias was assessed using Sycle’s risk of bias tool. A total of 13 in vivo preclinical studies of Lactobacillus spp. and Bifidobacterium spp. reported significant effectiveness in reducing seizure symptoms and regulating excitatory–inhibitory neurotransmitter balance in rat models of induced epilepsy. Probiotics have potential as effective alternative therapies in modulating seizure reduction and maintaining neurotransmitter balance during epilepsy. They may be developed in the future as non-pharmacological therapeutics based on microbiota.